(untitled) (Experimental biology, 2022)
Annotation The most important biological feature of beef bulls is their ability to consume and process a large amount of cheap low-nutritional feed, including waste from crop production and the food industry, into valuable food products for humans. The meat products and leather raw materials obtained at the same time are of high quality. The development of new directions in breeding, for example, early prediction of the productive qualities of livestock, contributed to a greater opportunity for selection, a reduction in the interval between generations and more effective breeding of cattle in the meat direction of productivity. We need animals that have requirements that provide for obtaining the most "economical animals", combining in their genotype the strength of the constitution and high productivity, good fattening and meat qualities, resistance and immunity to stress, having good adaptive abilities to living conditions and economic use. In other words, it is necessary to create animals with high productivity and well adapted to intensive use. The aim of the research was to improve and optimize breeding methods to increase the rate of genetic progress of different beef breeds of cattle. Based on the interaction of genotypes, to determine effective methods for improving the breeding and productive qualities of meat breeds of different genotypes to increase the production of high-quality beef. This article presents the results of studies of meat productivity of beef bulls of different genotypes in the conditions of the agricultural holding "Baiserke-Agro". According to the results of the research, the quality of carcasses and slaughter indicators, the morphological composition of carcasses and individual anatomical parts, the chemical composition of meat and the energy value of raw fat were established. The conducted studies contributed to the fullest realization of the genetic potential of the productivity of the Aberdeen Angus, Hereford and Kazakh white-headed breeds, as a result, an additional reserve for obtaining high-quality beef was revealed. The proposed methods and techniques of organizing the breeding process allowed to create highly productive beef cattle in the conditions of the agricultural holding "Bayserke-Agro", which contributed to reducing the cost of 1 kg of live weight gain by 5-8% and obtaining additional profit for 1 head by 14-16%.